2019
DOI: 10.1029/2019gl084730
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Buffers Decreasing Glacier Melt in an Andean Watershed—But Not Forever

Abstract: Accelerating mountain glacier recession in a warming climate threatens the sustainability of mountain water resources. The extent to which groundwater will provide resilience to these water resources is unknown, in part due to a lack of data and poorly understood interactions between groundwater and surface water. Here we address this knowledge gap by linking climate, glaciers, surface water, and groundwater into an integrated model of the Shullcas Watershed, Peru, in the tropical Andes, the region experiencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 77 publications
(105 reference statements)
2
58
0
1
Order By: Relevance
“…Saberi et al (2019) use field data and numerical modeling of a proglacial headwater catchment on Volcán Chimborazo in Ecuador to estimate that 18% of groundwater discharge is sourced from glaciers which cover 34% of the watershed area. Somers et al (2019) examine a proglacial watershed in the tropical Andes of Peru and estimate that glaciers contribute approximately 2% of groundwater discharge to the Shullcas River which has approximately 2% basin glacier coverage. Using contrasting methods, Liljedahl et al (2017) examined two glacierized watersheds in the Alaska Range.…”
Section: Recharge From Glaciersmentioning
confidence: 99%
See 1 more Smart Citation
“…Saberi et al (2019) use field data and numerical modeling of a proglacial headwater catchment on Volcán Chimborazo in Ecuador to estimate that 18% of groundwater discharge is sourced from glaciers which cover 34% of the watershed area. Somers et al (2019) examine a proglacial watershed in the tropical Andes of Peru and estimate that glaciers contribute approximately 2% of groundwater discharge to the Shullcas River which has approximately 2% basin glacier coverage. Using contrasting methods, Liljedahl et al (2017) examined two glacierized watersheds in the Alaska Range.…”
Section: Recharge From Glaciersmentioning
confidence: 99%
“…High mountain communities are already experiencing climate change impacts and are particularly vulnerable (Gurgiser et al, 2016;Heikkinen, 2017). Though groundwater provides some resilience to high mountain water resources, it is also vulnerable to long-term climate change (Somers et al, 2019).…”
Section: Representing Heterogeneitymentioning
confidence: 99%
“…The recent study of Christensen, Hayashi, and Bentley (2020) identified that in a talus‐moraine feature in the Canadian Rockies, groundwater from the moraine supplies most of the water to the basin outlet springs and that moraine, located downstream the talus, could serve as a “gate keeper” of the basin. While knowledge alpine hydrogeology is advancing with more and more studies, current knowledge remains limited and difficult to extrapolate to other alpine areas (Christensen et al, 2020; Somers et al, 2019). As a result, most studies about alpine areas oversimplify groundwater processes in hydrological models.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies indicate that climate change could cause long‐term decline of proglacial aquifer storage due to reductions in diffuse recharge, from rainfall and snow melt (Somers, Mckenzie, Mark, & Lagos, 2019), and in focused recharge from glacier‐fed river channels (Liljedahl, Gädeke, O'Neel, Gatesman, & Douglas, 2017). The dynamic behaviour of proglacial aquifer storage dynamics (e.g., intra‐annual variability) will also change in response to regional precipitation variability and meltwater runoff dynamics (Allen, Whitfield, & Werner, 2010).…”
Section: Introductionmentioning
confidence: 99%